The effects of entrepreneurial competencies on microenterprise performance in the southern border provinces of Thailand - Lateh, Muklis. author (School of Business Innovation & Technopreneurship, 2018)
This study is limited to Thailand, the country which is known as a developing country. Economically, the country is based on agriculture, tourism, industries, and micro sectors. There are 77 existing provinces in Thailand; this study focuses on 3 southern border provinces including Pattani, Yala, and Narathiwat. These particular areas are among the 20 poorest provinces in Thailand and have the highest rate of poverty in the country. This is due to the fact that most Muslim people are located here and microenterprises are operated in these areas. Furthermore, this study intentionally focuses on entrepreneurship development. Entrepreneurship provides job options for those who see opportunities and those who need a source of income. Entrepreneurs have an impact on the economy as current and future employers, and as suppliers, customers, and service providers for other enterprises, increase income, creating value and employment beyond their own enterprises. Generally, entrepreneurship development can be divided into many categories and one of them is microenterprise development. Thus, this study is limited to the microenterprise which is involved in low and middle-income level or poor people. In doing so, this study attempts to investigate the performance of the microenterprise. Finally, the study is limited to the information obtained from the local microenterprises in the southern border provinces of Thailand.